Association between self-assessment and clinical oral health status in adults, Paraguay. - Clarisse Díaz-Reissner; Juan Roldán-Merino; Irma Casas-García (Universidad de Concepción., 2020)
Introduction: Oral health can be defined as the absence of pathologies and disorders that affect the stomatognathic system. Objetives: This study aimed to determine the characteristics of self-assessment oral health status, in the clinical experience of dental caries, periodontal status, periodontal fixation loss and to investigate the association between self-reported and clinical oral health status among Paraguayans adults during early 2017. Material and Methods: The design is cross-sectional. Two dentists carried out the oral examinations following the recommendations of the World Health Organization (WHO). Results: There were 333 adult participants with a mean age of 35 ± 13 years. Most (77.2%) of the participants were female. Missing teeth (5.32±6), filled teeth (3.56±4), and decayed teeth (2.55±3) were also detected. Almost half (48.0%) of participants had dental calculus, while 5.8% had a periodontal pocket and 48.6% periodontal fixation loss. The self-perception of oral health was poor in 12.3% of participants, fair in 29.8%, normal in 31.8%, good in 16.2%, and excellent in 9.9%. Oral health self-assessment was positive in 58.0% and negative in 42.0%. A statistically significant difference was found when comparing the DMFT index according to self-perception of oral health, the score being higher in those who had negative self-perception; obtaining similar results in the decayed component. Conclusion: Negative oral health self-perception was associated with a high DMFT index, of this, the decayed component was the only one that presented statistically significant differences.